Time spent on documenting quality indicator data and associations between the perceived burden of documenting these data and joy in work among professionals in intensive care units in the Netherlands: a multicentre cross-sectional survey - Iwan C C van der Horst; Marieke Zegers; Johannes G van der Hoeven; Oscar Hoiting; Rutger Verhage; Eva Verweij; Inge Janssen; Brigitte Westerhof; Gilian Ambaum; Paul de Jong; Nynke Postma (BMJ Open, 2023)
Objectives The number of indicators used to monitor and improve the quality of care is debatable and may influence professionals’ joy in work. We aimed to assess intensive care unit (ICU) professionals’ perceived burden of documenting quality indicator data and its association with joy in work.Design Cross-sectional survey.Setting ICUs of eight hospitals in the Netherlands.Participants Health professionals (ie, medical specialists, residents and nurses) working in the ICU.Measurements The survey included reported time spent on documenting quality indicator data and validated measures for documentation burden (ie, such documentation being unreasonable and unnecessary) and elements of joy in work (ie, intrinsic and extrinsic motivation, autonomy, relatedness and competence). Multivariable regression analysis was performed for each element of joy in work as a separate outcome.Results In total, 448 ICU professionals responded to the survey (65% response rate). The overall median time spent on documenting quality data per working day is 60 min (IQR 30–90). Nurses spend more time documenting these data than physicians (medians of 60 min vs 35 min, p<0.01). Most professionals (n=259, 66%) often perceive such documentation tasks as unnecessary and a minority (n=71, 18%) perceive them as unreasonable. No associations between documentation burden and measures of joy in work were found, except for the negative association between unnecessary documentations and sense of autonomy (β=−0.11, 95% CI −0.21 to −0.01, p=0.03).Conclusions Dutch ICU professionals spend substantial time on documenting quality indicator data they often regard as unnecessary. Despite the lacking necessity, documentation burden had limited impact on joy in work. Future research should focus on which aspects of work are affected by documentation burden and whether diminishing the burden improves joy in work.